Insertion of Norplant ith and withoul prophylactic antibiotics: A randomized C011 ironed siudy - Risanto Siswosudarmo, Risanto Siswosudarmo (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 1992)
A randomized controlled study on the insertion of Norplant without prophylactic antibiotics had been carried out. The aim of the study was to compare the risk of complication happening shortly after insertion. A total of 500 acceptors completed their follow-up, 244 belonged to the antibiotic group (tetracycline), while 256 belonged to the control group. They come from suburban areas stuTounding the city of Yogyakarta.Insertion was carried out outside the hospital during the Safari Mass Campaign, with hospital standard asepsis. Follow-up was carried out one week after insertion to detect the presence of such complication or side effects as pain, inflammation, abscess and sense of itching. Data were processed with version 2.0 SPSS program using Nikon PC Computer. t-test, chi-square test and relative risk were statistical analysis used in the study.Results showed that both groups were comparable in. terms of age, body weight, parity, duration of insertion and level of education. The overall incidence of complication in the non-an tibiotic group was 19,9% compared to 24.2% in the antibiotic group (RRO.82, 95% CL 0.57Ã¢â¬â L19) . More detailed complications such as pain, inflammation, abscess and sense of itching show neither clinical nor statistical significant differences. The risk of complication in all, cases was influenced neither by duration of insertion nor by acceptors level of education.The study concluded that the insertion of Norplant without prophylactic antibiotics was as safe as with antibiotics.Key Words: Norplant - contraceptive mass campaign - antibiotics - obstetrics - contraceptive complication